Methods of detecting the veterinary drugs residues and the ways of reducing their content in food products. Review - N. L. Vostrikova; D. V. Khvostov; D. A. Utyanov; V. A. Zakharova; R. P. Bulgakov; A. V. Zherdev (Теория и практика переработки мяса)
The review was prepared in order to systematize the knowledge obtained in the recent years by the scientists from all over the world in the field of veterinary drugs application in the animal husbandry and the ways of management of their content in food products. It includes information on almost all currently known groups of antibiotics applied in animal husbandry, it considers the ways to reduce their amount in raw materials and / or the finished products, and describes the methods and procedures used to detect the residues of the veterinary drugs in raw materials and food products. It is not possible to run modern animal husbandry without the veterinary drugs. The global application of the veterinary drugs in animal husbandry exceeds 12 thousand tons, most of which are antibiotics for the infectious diseases treatment or prevention. Using the antibiotics in rearing the farm animals has led to the problem of their residues and / or metabolites in the raw materials and finished food products, which is why these food products cannot be considered safe for human consumption. The build-up of antibiotics in animal tissues depends on the group of the veterinary drug being used, and on the type of an animal. The content of residual amounts of some groups of antibiotics can be reduced by heat treatment of the meat. However, heat treatment can lead to the formation of new compounds that are potentially dangerous for the human health. Various analytical methods are used to determine the content of residual amounts of veterinary drugs in the food products, including enzyme immunoassay, chromatographic methods, biosensors and microbiological methods. The methods reviewed here for detecting the residual amounts of antibiotics in food products have their own advantages and disadvantages. In general, modern methods can currently detect the residues in food products of all known groups of antibiotics, used in animal husbandry, but it is necessary to keep on working on their improvement.